Assessment of flood discharges on small basins in sahelian and tropical countries. Data analysis and proposals for flood estimation - (:unkn) unknown (My University, 1996)
The aim of this study on floods in sahelian and tropical african catchments is to analyse the uncertainty in the estimation of instantaneous maximum flood discharges with a return period of 10 years. It also proposes a method to give the sizes for hydraulic works, taking out by Orstom (France) from 1955-1960 (Dubreuil, 1972). Two types of region are considered depending on their mean annual rainfall, P an : the sahelian and dry tropical regions (P an < 1000 mm) and the wet tropical regions (P an > 1000 mm). The relationships between the hydrological and geomorphological characteristics are examined and discussed for each region. In the main the flow coefficient and recession are discussed. The former is shown to be very difficult to assess when numerous data are not available, the latter seems easier to determine. The method which is suggested to dimension spillways employs the recession coefficient. It also considers the uncertainty of the correlations which are used to estimate the maximum flood discharges.
Keywords: African Research